284 Effectiveness of Webinar to Provide an Insight on the UK Surgical Training Pathways for the International Medical Graduates (IMGs) From Lower- & Middle-Income Country (LMIC). (19th August 2022) - Karki, BB; Gurung, D; Bista, A; Raj Shrestha, O; Limbu, R; Malla, S; Khanal, P; Aryal, K
Abstract: Aim: To provide an insight on the UK- Surgical Training Pathways for the International Medical Graduates (IMGs) from Lower- & Middle-Income Country (LMIC's). To eliminate the barriers for the effective and safe patient care. Method: A webinar "PLAB & Beyond" was organised by Nepalese Doctors Association-UK on 11 th Dec.2021 to provide an insight on various aspects of NHS and Training application process for Aspiring Surgeons from LMIC's. Virtual sessions were designed to share the first-hand experience by IMG's on varied NHS roles. A tailored session on Surgical Training pathways and application process was delivered by the IMG currently on the General Surgery Training Pathway. Results: There were 70 participants of various grades joining from 3 different continents. The pre-webinar questionnaire suggested that almost 85% of the IMG's were not oriented regarding the General Surgery Training Pathways. Only 30% had a very limited idea about the Surgical-Portfolio Scoring system. 55% thought it was impossible to get into the Surgical Training Pathway in the UK for an IMG. Post webinar feedback suggested that majority of the attendees (∼95%) acknowledged that the webinar enhanced their understanding of NHS and Surgical Training Pathway meeting the aims & learning outcomes. Conclusion: As IMGs from LMIC's contribute to major work force in the NHS, proper orientation to the training pathways must be added during local hospital induction. These session in broader sense will also aid to provide improved and equitable surgical care across international health system advocating Global Surgery, the 'Neglected stepchild of global health'.